Changing Trends in Maxillofacial Trauma: A Single-Center Retrospective Study in India - Kapil S. Agrawal; Vivek Gupta; Mudunuri Ravi Teja; Raghav Shrotriya; Vinita A. Puri (Indian Journal of Plastic Surgery)
Background Maxillofacial trauma is quite commonly encountered either in isolation or in association with polytrauma. The present observational study aims to analyze the changing trends of maxillofacial injuries and mull over some probable reasons for the same.